Manila by Night as Thirdspace - Campos, Patrick F. (Archīum Ateneo, 2024)
The Marcosian signifier in Manila by Night has been inescapably registered in the production, distribution, and exhibition of the film and in the film text itself. The paper revisits these evaluations of the film by using Edward Soja’s broader notion of “thirdspace.” It rereads Manila by Night as Bernal’s concept of the city which approximates the lived dimension of urban spaces vis-à-vis the “concept city” of the Marcoses. Such a revaluation of Manila by Night as thirdspace 1) locates the film at the center of wider spatio-temporal interrelationship—from “global” to “national” to “cinematic” space, and 2) salvages the epistemological concerns of Bernal, which previous critiques of Manila by Night tended to eclipse.